Beyond the Middle Kingdom : Comparative Perspectives on China's Capitalist Transformation. - Kennedy, Scott (Stanford University Press, 2011)
This book breaks new ground by systematically examining China's capitalist transformation through several comparative lenses. The great majority of research on China to date has consisted of single-country studies. This is the result of the methodological demands of studying China and a sense of the country's distinctiveness due to its grand size and long history. The moniker Middle Kingdom, a direct translation of the Chinese-language word for China, is one of the most prominent symbols of the country's supposed uniqueness.Composed of contributions from leading specialists on China's politica.